Clinicopathologic significance of epithelio-mesenchymal transition in human lung adenocarcinomas: An integrative analysis, inclusive of genetic alterations, on 256 surgically resected cases. (2017) - Menju, Toshi; Sowa, Terumasa; Sonobe, Makoto; Miyata, Ryo; Takahashi, Koji; Nishikawa, Shigeto; Nakanishi, Takao; Neri, Shinya; Cho, Hiroyuki; Hamaji, Masatsugu; Hijiya, Kyoko; Motoyama, Hideki; et al.
Abstract: Introduction: Prior studies have shown that the activation of epithelio-mesenchymal transition (EMT) in tumor cells induces their invasive and metastatic properties. In our study, we aimed to elucidate the clinicopathologic significance of EMT in lung adenocarcinomas. Patients and methods: Clinical samples were obtained from 256 cases of lung adenocarcinomas that were consecutively resected from 2001 to 2007 at Kyoto University Hospital. Tissue microarrays of these samples were immunohistochemically stained for E-cadherin and vimentin, and classified into three groups, named "Full", "Partial", "Null", based on the combined expression of these two markers, which is indicative of tumor EMT activation level. DNA was extracted from surgical specimens, and the mutations in the hot-spot exons of EGFR, ALK, K-ras, and p53 were detected by single-strand conformation polymorphism or direct sequencing. Results: Group "Full" exhibited the highest positivity in terms of local lymph-vascular involvements and lymph node metastases, followed by groups "Partial" and "Null, " respectively. Significant differences in overall and disease-free survivals (OS, DFS) were seen among these 3 groups. Poorly differentiated adenocarcinomas and heavy smoking status had strong associations with the EMT level. Tumors harboring mutant EGFRs showed less EMT activation. In statistical analyses, EMT was a significant factor both in logistic regression models for the prediction of lymph node metastases, as well as, in Cox hazard models for OS and DFS for exclusion of node metastasis. Conclusions: The activation of EMT in human lung adenocarcinomas plays pivotal roles in their malignant progression. EMT is an appropriate target for the improvement of prognosis. Microabstract: The significance of epithelio-mesenchymal transition in lung adenocarcinoma remains controversial in clinical settings. We retrospectively studied the combination of epithelial and mesenchymal markers on 256 patients. The EMT activation levels showed a trend for pathologic local invasiveness, node metastases, and poor survival. These findings suggest that EMT is the challenging target for the malignant progression, and is worth further investigation.